Case report of nivolumab-related pneumonitis. (March 2017) - Tada, Kohei; Kurihara, Yasuyuki; Myojo, Tomohiro; Kojima, Fumitsugu; Ishikawa, Yuya; Yoshiyasu, Nobuyuki; Morimoto, Masaya; Ito, Reiko; Koyamada, Ryosuke; Yamashita, Takuya; Bando, Toru; Mori, Shinichiro; et al.
We report a case with suggestive antiprogrammed death-1 inhibitor-related pneumonitis in an endometrial cancer patient. This case presented with fever and cough after three dosages of nivolumab. Computed tomography initially showed centrilobular nodularities in a unilateral lung, which was compatible with aspiration pneumonia. However, diffuse ground-glass opacities (GGO) rapidly developed in the unilateral lung over 4 days despite the use of broad-spectrum antibiotics. Development of GGO was considered to be related to a nivolumab-mediated immune reaction. Corticosteroid was administered and the GGO subsequently disappeared. The present report focuses on the computed tomography diagnostic features of nivolumab-related pneumonitis. The accumulation of knowledge regarding various types of antiprogrammed death-1-related pneumonitis will lead to appropriate treatment for this newly emerging adverse event.